MECHANISMS FOR THE FORMATION OF SPIRITUAL STABILITY IN THE EDUCATIONAL PROCESS OF STUDENTS (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses thoughts and reflections on the mechanisms of forming spiritual stability in students during the learning process. In today's rapidly evolving world, the importance of spiritual stability, particularly among students, cannot be understated. As individuals transition from adolescence to adulthood, they encounter various challenges and pressures that may affect their emotional, mental, and spiritual well-being. Therefore, fostering spiritual stability becomes a critical aspect of education. Before delving into the mechanisms, it is essential to define spiritual stability. Spiritual stability refers to a person's ability to maintain a sense of inner peace, balance, and resilience in the face of life's challenges.